2008
DOI: 10.1111/j.1469-8137.2008.02693.x
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium sorption, influx, and efflux at the mesophyll layer of leaves from ecotypes of the Zn/Cd hyperaccumulator Thlaspi caerulescens

Abstract: Summary• Differential sorption and transport characteristics of the leaf mesophyll layer of the Prayon and Ganges ecotypes of the hyperaccumulator Thlaspi caerulescens were examined.• 109 Cd influx and efflux experiments were conducted with leaf sections, and X-ray absorption near edge structure (XANES) data were collected from leaves as a general comparison of in vivo cadmium (Cd) coordination.• There were modest differences in cell wall sorption of Cd between ecotypes. There were obvious differences in time-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
32
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 49 publications
1
32
0
Order By: Relevance
“…The net Zn-uptake rate increased as the Zn-concentration in the growth solution increased, because the greater the external concentration of Zn, the higher were both Zn-influx and Zn-efflux (Santa-Maria & Cogliatti, 1998). In addition, the enhancement of Cd uptake under dually Zn and Cd treatment might be attributed to an altered and specialized transporter of metal ions in the plasma membrane system induced by the addition of Zn (Ebbs et al, 2009). …”
Section: Zinc Accumulationmentioning
confidence: 99%
“…The net Zn-uptake rate increased as the Zn-concentration in the growth solution increased, because the greater the external concentration of Zn, the higher were both Zn-influx and Zn-efflux (Santa-Maria & Cogliatti, 1998). In addition, the enhancement of Cd uptake under dually Zn and Cd treatment might be attributed to an altered and specialized transporter of metal ions in the plasma membrane system induced by the addition of Zn (Ebbs et al, 2009). …”
Section: Zinc Accumulationmentioning
confidence: 99%
“…This mainly involves the TcZNT5 metal transporter, which is more abundant in the plasma membrane of epidermal storage cells than in other cell types (Leitenmaier and Küpper 2011). Although epidermal storage cells can have higher metal concentrations than mesophyll cells, it is the mesophyll tissue layer that harbours the greater total mass of metal Vogel-Mikuš et al 2008;Ebbs et al 2009). The involvement of the leaf mesophyll in metal hyperaccumulation and tolerance is reasonable, as mesophyll cells are much more abundant and are positioned between the vascular bundles (representing a source of metals in the leaves after xylem loading) and the epidermal cells (Ebbs et al 2009).…”
mentioning
confidence: 99%
“…Although epidermal storage cells can have higher metal concentrations than mesophyll cells, it is the mesophyll tissue layer that harbours the greater total mass of metal Vogel-Mikuš et al 2008;Ebbs et al 2009). The involvement of the leaf mesophyll in metal hyperaccumulation and tolerance is reasonable, as mesophyll cells are much more abundant and are positioned between the vascular bundles (representing a source of metals in the leaves after xylem loading) and the epidermal cells (Ebbs et al 2009). In a study that compared Cd sorption and transport characteristics in the leaf mesophyll layer of the N. caerulescens ecotypes of Prayon (Zn/Cd hyperaccumulator) and Ganges (Cd/Zn hyperaccumulator) (Ebbs et al 2009), a clear difference in Cd efflux between these two ecotypes was shown, with Prayon showing higher efflux rates.…”
mentioning
confidence: 99%
See 2 more Smart Citations